A case of a rectal stricture related to ischemic proctitis following rupture of an aortic aneurysm - Iida, Tomoya; Ohkubo, Yosuke; Kubo, Toshiyuki; Yamashita, Kentaro; Onodera, Kei; Yamamoto, Eiichiro; Nosho, Katsuhiko; Ito, Toshiro; Yamano, Hiroo; Nakase, Hiroshi (Endoscopy International Open, 2018)
Background and study aims Ischemic proctitis is a rare disease and comprises 2 % to 5 % of cases of ischemic colitis, because the rectum has abundant blood supply and rich collaterals. Herein, we report a case of a 73-year-old male patient with a pronounced rectal stricture caused by ischemic proctitis resulting from an abdominal aortic rupture and treated by endoscopic balloon dilation therapy. To date, only 3 cases of rectal stricture related to ischemic proctitis including our case have been reported, and this is the first case of rectal stricture related to ischemic proctitis, which was successfully treated by endoscopic balloon dilation.